1993
DOI: 10.1016/0014-5793(93)81707-7
|View full text |Cite
|
Sign up to set email alerts
|

Rab11, a small GTPase associated with both constitutive and regulated secretory pathways in PC12 cells

Abstract: A specific polyclonal antibody was used to investigate the subcellular distribution of the small GTPase, rabl 1 p, in the neuroendocrine cell line, PC12. We took advantage of a previously described pulse-chase protocol based on sulfation [1] to examine the distribution of rabl 1 along the secretory pathway. Using the rabl 1 antiserum, but not serum depleted of rabl 1 antibodies, we were able to specifically immunoisolate markers of the constitutive and the regulated secretory pathway in the trans-Golgi network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
141
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 29 publications
11
141
0
Order By: Relevance
“…In this re-spect it is interesting to note that rab5, which has a high intrinsic GTPase activity and rapidly cycles between the GTP and GDP-bound form on membranes (Rybin et al, 1996), is relatively insensitive to release by GDI under our assay conditions (our unpublished results). In contrast, both rab7 and rab11 have significantly slower intrinsic GTPase activities (Urbé and Parton, 1995;Simon et al, 1996), yet both are sensitive to release from membranes by excess GDI (our unpublished results). Taken together, the data hint that the factors involved in stable membrane recruitment, including GDI displacement factor and guanine nucleotide exchange factor, may be the most critical in dictating the GDP-/GTP-bound ratio of an individual rab protein.…”
Section: Rab11 As a Select Target Of Gdi In Vivomentioning
confidence: 71%
See 3 more Smart Citations
“…In this re-spect it is interesting to note that rab5, which has a high intrinsic GTPase activity and rapidly cycles between the GTP and GDP-bound form on membranes (Rybin et al, 1996), is relatively insensitive to release by GDI under our assay conditions (our unpublished results). In contrast, both rab7 and rab11 have significantly slower intrinsic GTPase activities (Urbé and Parton, 1995;Simon et al, 1996), yet both are sensitive to release from membranes by excess GDI (our unpublished results). Taken together, the data hint that the factors involved in stable membrane recruitment, including GDI displacement factor and guanine nucleotide exchange factor, may be the most critical in dictating the GDP-/GTP-bound ratio of an individual rab protein.…”
Section: Rab11 As a Select Target Of Gdi In Vivomentioning
confidence: 71%
“…In nonpolarized cells rab11 was found associated with both the Golgi and the recycling en-dosome Ren et al, 1998). In polarized and regulated secretory cells rab11 has been localized to the Golgi as well as a variety of specialized membrane compartments (Urbé et al, 1993;Deretic et al, 1996;Goldenring et al, 1996Goldenring et al, , 1997Sheehan et al, 1996;Calhoun and Goldenring, 1997). The complex localization profiles of rab11 in diverse cell types have complicated the assessment of its precise function in intracellular membrane transport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No detectable signal could be observed in the nuclear and PM (Figure 3A a, e, i, m). It also showed that there was a colocalization of rSac3 with concanavalin A (ConA), an ER marker ( Figure 3A a-d) [37], MCFD2, the ER-Golgi intermediate compartment marker (Figure 3A e-h) [35], WGA, a Golgi complex marker ( Figure 3A i-l) [38] and Rab11, a trans-Golgi network and recycling endosome marker ( Figure 3A m-p) [39,40]. No colocalization of rSac3 with the early endosome marker early endosomal antigen 1 (Supplementary information Figure S1D-F) [41], the late endosome marker mannose 6-phosphate receptor Figure S1G-I) [7] or the lipid fraft marker caveolin-1 [42] could be detected.…”
Section: Rsac3 Is Localized To the Er Golgi Complex And Recycling Enmentioning
confidence: 92%